Rancangan Strategi Pemasaran Laboratorium Kesehatan Provinsi Sumatera Utara Berdasarkan Analisis SWOT Tahun 2020 - Eva Carolina Sitompul (Jurnal Kajian Kesehatan Masyarakat, 2020)
Regional Health Laboratory of North Sumatra Province as the Technical Implementing Unit (UPT) of the North Sumatra Province Health Office with the main task of organizing and improving health laboratory service efforts in North Sumatra Province and is an integral part of health services that play a role in supporting health efforts. In the last 5 years the number of service users tends to decrease by many competitors, the marketing program has not yet existed. The purpose of this study is to analyze internal factors (strengths and weaknesses) and external factors (opportunities and threats), the marketing strategy design of the North Sumatra Province health laboratory. This type of research is qualitative with a descriptive exploratory approach.Data collection techniques with observation, in-depth interviews and documentation. Informants in this study there were 6 people selected by purposive sampling. Data analysis techniques with data collection, qualitative analysis and SWOT analysis (strength, weakness, opportunity, threat), SWOT matrix, Cartesian diagram to determine the position of the North Sumatra Province Health Laboratory and the compilation of an appropriate strategic plan. he results of the study showed that the total score of strength was 1.82 and weakness was 0.63 so that the x-axis gained 1.19, which means that strength was higher than weakness. The total score of odds was 1.78 and the threat score was 0.56 so that the y-axis was 1,22 means that the opportunity factor is greater than the threat By using the Cartesian diagram it can be concluded that the North Sumatra Provincial Health Laboratory is in quadrant 1, this position is very advantageous because it can utilize all the power to seize the opportunities that exist. So the most appropriate strategy to be implemented now is the strategy which supports an aggressive growth policy (Growth Oriented Strategy). It is recommended to continue to improve the quality of service oriented to customer satisfaction more aggressively forming a marketing team and the availability of marketing funds so that the program of marketing strategy activities can run effectively.